2021
DOI: 10.3389/fpls.2021.756068
|View full text |Cite
|
Sign up to set email alerts
|

Differential Functions of Pepper Stress-Associated Proteins in Response to Abiotic Stresses

Abstract: Stress-associated proteins (SAPs), a group of zinc-finger-type proteins, have been identified as novel regulators of plant abiotic and biotic stresses. However, although they have been discovered in different plant species, their precise functional roles remain unclear. Here, we identified 14 SAP subfamily genes in the pepper genome. An investigation of the promoter regions of these genes for cis-regulatory elements associated with abiotic stress responses revealed the presence of multiple stress-related eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 91 publications
(130 reference statements)
1
16
0
Order By: Relevance
“…The accumulation of CaSAP14 transcripts was induced at 2 or 6 h post‐treatment. In addition, we extended our previous examination of the organ‐specific expression of CaSAP14 (Bae et al., 2021), which revealed that CaSAP14 expression was differentially induced in different pepper organs, with the highest levels being detected in petioles, flowers, and seeds (Figure 3b). In addition, we sought to determine the subcellular localization of CaSAP14 protein by transiently expressing GFP‐tagged CaSAP14 in the leaves of N. benthamiana plants.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…The accumulation of CaSAP14 transcripts was induced at 2 or 6 h post‐treatment. In addition, we extended our previous examination of the organ‐specific expression of CaSAP14 (Bae et al., 2021), which revealed that CaSAP14 expression was differentially induced in different pepper organs, with the highest levels being detected in petioles, flowers, and seeds (Figure 3b). In addition, we sought to determine the subcellular localization of CaSAP14 protein by transiently expressing GFP‐tagged CaSAP14 in the leaves of N. benthamiana plants.…”
Section: Resultssupporting
confidence: 72%
“…Given the auto‐activity of full‐length CaSnRK2.6, we used a C‐terminal truncated CaSnRK2.6 fragment (amino acids 1–320: CaSnRK2.6 A320) for the purposes of Y2H screening and accordingly identified several interacting partner proteins, among which was CA10g19590, a protein annotated as a member of the SAP family. Previously, we isolated 14 SAP genes in C. annuum (Bae et al., 2021). In the present study, we named them, based on groups and the order of chromosomal loci within groups (CaSAP1, CA01g04040; CaSAP2, CA02g10410; CaSAP3, CA03g17080; CaSAP4, CA00g44110; CaSAP5, CA10g16510; CaSAP6, CA12g06430; CaSAP7, CA01g16220; CaSAP8, CA01g19950; CaSAP9, CA10g20690; CaSAP10, CA01g19980; CaSAP11, CA12g22410; CaSAP12, CA02g29220; CaSAP13, CA05g01100; CaSAP14, CA10g19590).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations